2018
DOI: 10.1186/s12938-018-0517-1
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic performance within crossed stent grafts: computational and experimental study on the effect of cross position and angle

Abstract: Background and aimsThe crossed limbs stent graft technique is regularly employed to treat abdominal aortic aneurysm patients with unfavorable aneurysm necks or widely splayed common iliac arteries. This article numerically evaluates the hemodynamic performance of the crossed limbs strategy by analyzing numerical simulations and conducting experiments using two series of idealized bifurcated stent grafts with different cross angles and cross positions.ResultsResults demonstrated that the absolute helicity at ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Additionally, the high OSI area, which decreased with the increase in the aneurysm neck angle in a proportional manner, was mainly concentrated at the proximal end of the iliac limb SGs. High OSI area was reported to cause platelet aggregation, increase the retention time of coagulation-promoting particles and result in thrombosis ( Nordgaard et al, 2010 ; Liu et al, 2018 ). Therefore, we speculate that there may be a risk of thrombosis in the proximal end of the iliac limb SGs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the high OSI area, which decreased with the increase in the aneurysm neck angle in a proportional manner, was mainly concentrated at the proximal end of the iliac limb SGs. High OSI area was reported to cause platelet aggregation, increase the retention time of coagulation-promoting particles and result in thrombosis ( Nordgaard et al, 2010 ; Liu et al, 2018 ). Therefore, we speculate that there may be a risk of thrombosis in the proximal end of the iliac limb SGs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the neck angulation may be coronal and/or sagittal; namely, the hemodynamic alteration from a conventional non-cross EVAR may be caused by different spatial azimuths. However, previous hemodynamic studies on the cross and non-cross EVAR mostly adopted idealized and realistic models without neck angulation ( Georgakarakos et al, 2014 ; Stefanov et al, 2016 ; Liu et al, 2018 ). Moreover, although there have been comparative studies using patient-specific EVAR models in which necks may be angulated, a particular AAA has individualized geometry, and other geometric features (including the stent configuration) may cause the hemodynamic differences between the cross and non-cross SGs ( Efstratios, 2012 ; Stefanov et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The no-slip condition was imposed on the surface of the models according to the rigid wall assumption [ 28 ]. It was shown that the maximum DF and peak pressure drop arose at peak pressure throughout the cardiac cycle [ 29 , 30 ]. As a result, a constant velocity of v = 0.1 m/s was applied at the inlets, and the pressure was set as 105 mmHg at the outlets, which characterized the moment of peak pressure throughout the cardiac cycle [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…C o m p u t e r-b a s e d s i m u l a t i o n h a s b e e n u s e d t o generate three-dimensional (3D) models and clarify the hemodynamics in patients with brain aneurysms, coronary artery aneurysms, and abdominal aortic aneurysms, among other conditions (9)(10)(11). However, it has not been used in ocular diseases.…”
Section: Introductionmentioning
confidence: 99%